Doing Business 2011 : Kuwait - World Bank Group (Washington, DC, 2014)
"Doing Business 2011 : Making a Difference for Entrepreneurs" is the eighth in a series of annual reports investigating regulations that enhance business activity and those that constrain it. "Doing Business" presents quantitative indicators on business regulations and the protection of property rights that can be compared across 183 economies: 46 in Sub-Saharan Africa, 32 in Latin America and the Caribbean, 25 in Eastern Europe and Central Asia, 24 in East Asia and Pacific, 18 in the Middle East and North Africa and 8 in South Asia, as well as 30 OECD high-income economies. A set of regulations affecting 9 stages of a business's life are measured: starting a business, dealing with construction permits, registering property, getting credit, protecting investors, paying taxes, trading across borders, enforcing contracts and closing a business. Other areas important to business such as an economy's proximity to large markets, the quality of its infrastructure services, the security of property from theft and looting, the transparency of government procurement, macroeconomic conditions or the underlying strength of institutions, are not studied directly by "Doing Business." The following pages present the summary Doing Business indicators for Kuwait. The data used for this economy profile come from the Doing Business database and are summarized in graphs. These graphs allow a comparison of the economies in each region not only with one another but also with the "good practice" economy for each indicator.